CITRULLINE MALATE IN MEDICAL AND SPORT APPLICATIONS - Paweł Radkowski; Urszula Justyna Wojciechowska; Adam Rafałowicz; Magdalena Rafałowicz; Paweł Jakub Wojciechowski; Łukasz Grabarczyk (International Journal of Innovative Technologies in Social Science, 2025)
Background. Nitric oxide has emerged as a key physiological signalling molecule that has a significant impact on vessels, skeletal muscle function and exercise performance. With this in mind, increasing its production is of great interest to clinicians and athletes, making citrulline malate a potential medication and one of the most popular ergogenic supplements. Aim. This article aims to review current knowledge on citrulline malate supplementation, with emphasis on its pharmacokinetics, proposed medical application and ergogenic benefits. Material and Methods. Literature search in PubMed and Google Scholar for clinical trials, meta-analyses, and reviews on citrulline malate using keywords: citrulline malate, nitric oxide, muscle endurance, medical applications, supplementation”. Results. Citrulline malate exhibit its positive impact on many medical conditions. In pulmonary hypertension by improving exercise tolerance and modestly reducing arterial pressure. In metabolic conditions, leading to better glycaemic control, improved lipid profiles, and reduced inflammation in diabetes. Men with mild erectile dysfunction report subjective improvements when using citrulline malate alone or alongside other therapies. In atherosclerosis, it increases the elasticity of the arteries, which becomes weaker in advanced disease. Beyond medical applications, citrulline malate supplementation is primarily known for supporting short-term, high-intensity exercise by delaying fatigue, improving endurance, lowering perceived exertion during resistance training and reducing post-workout muscle soreness. Conclusion: Citrulline malate could be used as medical application and can enhance exercise performance by delaying fatigue and reducing muscle soreness. Larger, rigorously controlled trials are required to establish optimal dosing, target activities and long-term safety.